INTEGRATION OF COST VOLUME PROFIT AND ACTIVITY BASED COSTING IN OBTAINING COST ACCURACY FOR DECISION MAKING - Andi Muliati; Syamsuri Rahim (Riset Akuntansi Keuangan, 2020)
This study aims to provide an explanation of how the integration of CVP and ABC can provide results of analysis and information that is more accurate than the traditional CVP on Elegant Photography to be used as a basis for decision making. The method used in this research is descriptive quantitative method by collecting data and information from the research location directly through interviews, observation and documentation. Furthermore, data and information analysis is obtained using cost volume profit analysis tools including break-even analysis, profit planning, margin of safety, shut down point, degree of operating leverage, and contribution margin and Activity based costing. The results obtained from this study provide the availability of more accurate and varied information. The CVP analysis results show the number of break-even points, earnings plans and contribution margins. As well as showing excellent performance in terms of the percentage of MOS and DOL while ABC analysis provides information about better cost accuracy so that the data and information from these two Terk can be the basis for strategic decision making for management